Transcriptional Profiling Reveals Brain Region-Specific Gene Networks Regulated in Exercise in a Mouse Model of Parkinson’s Disease - Tong, Weifang; Zhang, Kunshan; Yao, Hongkai; Li, Lixi; Hu, Yong; Zhang, Jingxing; Song, Yunping; Guan, Qiang; Li, Siguang; Sun, Yi E.; Jin, Lingjing (Frontiers in Aging Neuroscience, 2022)
Exercise plays an essential role in improving motor symptoms in Parkinson’s disease (PD), but the mechanism in the central nervous system remains obscure. We tested effects of 12-week treadmill exercise on a chronic 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced mouse model of PD and observed a significant improvement in motor ability. Then, we performed RNA sequencing on the 4 brain regions, including cortex, cerebellum, nigra and striatum. By employing an integrative network biology approach to identify transcriptional networks on the four regions, we found that nigra and striatum were remarkably different among individual regions response to exercise in PD. Specifically, synaptic regulation pathways about axon guidance, synapse assembly, neurogenesis, synaptogenesis, transmitter transport-related pathway and synaptic regulation genes, including Cisbp, Neurod2, Rtn4rl2 and Cd5 were up-regulated in nigra and striatum. Furthermore, we validated in vivo that exercise rescued loss of TH+ synapses in the striatal region in PD mice. This study provides a powerful genetic profile of four brain regions in PD and exercised PD by integrating large-scale transcriptomic data. Based on those evidences, transcriptional mechanisms relevant to pathological states during the exercise for PD subjects can be further investigated.